2021
DOI: 10.3390/cancers13112750
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Epithelial-Mesenchymal Phenotypes in Circulating Tumour Cells from Prostate Cancer Patient-Derived Xenograft Models

Abstract: Metastasis is the leading cause of cancer-related deaths worldwide. The epithelial-mesenchymal plasticity (EMP) status of primary tumours has relevance to metastatic potential and therapy resistance. Circulating tumour cells (CTCs) provide a window into the metastatic process, and molecular characterisation of CTCs in comparison to their primary tumours could lead to a better understanding of the mechanisms involved in the metastatic cascade. In this study, paired blood and tumour samples were collected from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 85 publications
0
39
2
Order By: Relevance
“…Previous studies indicated that the plasticity of EMT tumor cells, which are in a transitory state between epithelial and mesenchymal programs, made it possible to accomplish the invasion-metastasis cascade, rather than the mesenchymal-like tumor cells that have fully completed the EMT program (32,42). Compelling evidence showed that transforming growth factor b (TGF-b) is a potent inducer of EMT and chemoresistance in multiple cancers, including PCa, through small mothers against decapentaplegic homolog-independent or homolog-dependent signaling pathway (9,32,(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the plasticity of EMT tumor cells, which are in a transitory state between epithelial and mesenchymal programs, made it possible to accomplish the invasion-metastasis cascade, rather than the mesenchymal-like tumor cells that have fully completed the EMT program (32,42). Compelling evidence showed that transforming growth factor b (TGF-b) is a potent inducer of EMT and chemoresistance in multiple cancers, including PCa, through small mothers against decapentaplegic homolog-independent or homolog-dependent signaling pathway (9,32,(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, non-genetic determinants diversify cell populations into distinct phenotypes or cell states with various degrees of metastatic potential and resistance to various therapies [ 43 , 44 ]. Specifically, phenotypic heterogeneity along the EMT spectrum, or EM plasticity (EMP), is emerging as a distinctive feature of primary tumors [ 45 ], CTCs [ 46 , 47 ], and in the relation between tumors and CTCs [ 48 ]. This heterogeneity can arise due to diverse signaling cues that induce EMT in a spatio-temporal-dependent manner, as seen for instance in time course or wound healing experiments [ 36 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, liquid biopsy via isolation of CTCs represents a promising diagnostic tool capable of supplementing state-of-the-art PC diagnostics [ 40 ] and prognosis [ 41 , 42 , 43 , 44 , 45 ].…”
Section: The Role Of Dep For Ctc Detection In Prostate Cancermentioning
confidence: 99%